Relocating: the asylum experience in Cairo - Fiddian-Qasmiyeh, E (Taylor and Francis, 2006)
Refugees’ experiences of living in non-Western urban settings are infrequently addressed outside those particular cities. This essay presents snapshots of refugees’ experiences of asylum in one such city, Cairo, where it is UNHCR which undertakes the refugee status determination process. Following a presentation of the main institutional actors involved in Cairo’s ‘asylum scene’, it outlines some of the ‘general’ and ‘normal’ problems, vulnerabilities and risks encountered by refugees there. The remainder of the essay documents the particular difficulties experienced by three groups of sub-Saharan African refugees in this city: survivors of sexual and gender-based violence, unaccompanied minors and young men at particular risk. It demonstrates that, far from encountering peace through asylum, they discover a site characterized both by new forms of violence and by repetitions of existing abuse, and highlights the reasons why the right to legal counsel is one of the most important rights that a refugee can have.